A metallic nickel site in a complex multimetallic design for controlled CO2 reduction and symmetric supercapacitor device. (March 2023) - Patil, R.; Kumar, N.; Bhattacharjee, S.; Matsagar, B.M.; Han, P.-C.; Wu, K.C.W.; Salunkhe, R.R.; Bhaumik, A.; Dutta, S.
Abstract: Single metallic sites are promising for high power density with promising capacitive performance, and for low-energy chemical reduction of CO2 to formate. Here, we present a novel strategy for accessing C-ZIF-700 with metallic nickel (Ni) sites encapsulated by multiwalled nanotube shells from trimetallic imidazolate frameworks (M-ZIF). A X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) spectroscopic analysis confirmed the zero-valance state of Ni, with no significant positive valance state. C-ZIF-700 showed no sign of leaching of Ni nanoparticles under aqua regia treatment for long, as evidenced from -XANES-EXAFSanalysis. It is demonstrated that the coexistence of Ni and Co in C-ZIF-700 renders more active electrochemical energy storage by regulating charge distribution to improve electronic transportation capability. C-ZIF-700 with predominantly metallic Ni-sites demonstrated superior capacitive performance, presenting a remarkable capacitance value of 262 F/g at a scan rate of 5 mV/s. In an assembled symmetric supercapacitor device, C-ZIF-700 exhibited a very high specific energy value of 21.2 Wh/kg at a current density of 0.05 A/g, which retained up to 9.7 Wh/kg at 10 A/g, and a corresponding specific power value of 25 kW/kg. C-ZIF-700 has offered facile N-formylation of the primary amine group of aniline, with the assistance of alkyl silane as a hydride source under moderate CO2 pressure (15–20 bar) and temperature (maximum 100 °C). Electronic structural evidence of metal sites in C-ZIF-700, by using XANES-EXAFS, electron microscopy, and CO2 adsorption–desorption profile supports that Ni-site is responsible for CO2 activation-reduction. The evidence also supports a possible synergistic effect of Co nanoparticles in capacitance enhancement and CO2 reduction. This strategy, thus, proves the outstanding role of encapsulated Ni sites for enhanced capacitive performance and chemical fixation of CO2 . Graphical abstract: C-ZIF-700 with high loading of metallic Ni sites was obtained via solid-state pyrolysis of M-ZIF at 700 °C. Ni-sites enhances capacitive performance in a SSD as well as hydrosilylation reduction of CO2 to formate. Image 1 Highlights: Metallic nickel (Ni) sites encapsulated by multiwalled nanotube shells. Multimetallic design from M-ZIF, a trimetallic framework. Predominantly metallic Ni-sites demonstrated superior capacitive performance. Ni sites of chemical CO2 fixation by reduction to formate.